2012
DOI: 10.1007/s10008-012-1712-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preparation method on structure, morphology, and electrochemical performance of spherical Li[Ni0.5Mn0.3Co0.2]O2

Abstract: Spherical Li[Ni 0.5 Mn 0.3 Co 0.2 ]O 2 was prepared by both the continuous hydroxide co-precipitation method and continuous carbonate co-precipitation method under different calcined temperatures. The physical properties and electrochemical behaviors of Li[Ni 0.5 Mn 0.3 Co 0.2 ]O 2 prepared by two methods were characterized by X-ray diffraction, scanning electron microscope, and electrochemical measurements. It has been found that different preparation methods will result in the differences in the morphology (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…All the diffraction peaks can be well indexed based on the O3 type layered structure of a hexagonal NaFeO 2 with space group R 3m. 36,37 No signicant lattice parameter differences were observed between the pristine and LTP-coated material. However, there still appear some additional weak diffraction peaks between 20 and 25 , indicating a layered structure with Li 2 MnO 3 character (space group C2/m) and the ordering of Li, Ni, and Mn atoms in the transition metal layers.…”
Section: Resultsmentioning
confidence: 94%
“…All the diffraction peaks can be well indexed based on the O3 type layered structure of a hexagonal NaFeO 2 with space group R 3m. 36,37 No signicant lattice parameter differences were observed between the pristine and LTP-coated material. However, there still appear some additional weak diffraction peaks between 20 and 25 , indicating a layered structure with Li 2 MnO 3 character (space group C2/m) and the ordering of Li, Ni, and Mn atoms in the transition metal layers.…”
Section: Resultsmentioning
confidence: 94%
“…This demonstrates a similar cycling performance upon charging to 4.3 V to that of the cathodes that were synthesized using the precursor produced via ammonia-containing coprecipitation. 13,[42][43][44][45] The high-voltage cycling ability of cathode in the voltage region of 3.0-4.6 V was analysed in the electrolyte with 5 wt% FEMC as a high-voltage additive at the rates of 0.1C, 0.2C and 0.1C again for possible high-energy density battery applications. As displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Widely used coprecipitation synthesis of metal hydroxides includes the use of ammonia as a chelating agent 4,5,[7][8][9][10][11][12][13][14] forming transition metal-ammonia complexes and it proceeds in two steps: first, metal ions form a complex with ammonia aqueous solution, in which more than 0.2 M of ammonia water is used, as represented in eqn (1). Then, by anion exchange from ammonia to hydroxide anions that come from NaOH added, metal hydroxides precipitate slowly as in eqn (2).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high capacity, low toxicity and low cost, over the past twenty years, LiNiO 2 has been considered as an alternative cathode material to commercialized LiCoO 2 . [1][2][3][4][5] Nevertheless, pristine LiNiO 2 demonstrates poor thermodynamic stability, a property which hinders its commercialization. Through various research efforts, it was found that Co and Al co-doping can greatly improve its thermodynamic stability and electrochemical reactivity.…”
Section: Introductionmentioning
confidence: 99%